2016
DOI: 10.15192/pscp.sa.2016.13.1.4258
|View full text |Cite
|
Sign up to set email alerts
|

Influence of osmoregulators on plant tolerance to water stress

Abstract: CitationDawood MG. 2016. Influence of osmoregulators on plant tolerance to water stress, 13 (1), 42-58. Retrieved from www.pscipub.com (DOI: 10.15192/PSCP. SA.2016.13.1.4258) This article highlights on some recent researches, which studied the impact of osmoregulator compounds and their application on the plant in order to increase the plant tolerance to water stress. Water stress limits the growth, productivity and quality of agricultural crops in the world. Water Stress is not only due to the scarcity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
(63 reference statements)
1
2
0
Order By: Relevance
“…Similar to our findings, the reduction of MDA and H 2 O 2 contents were also observed in some plants using GB(El-Samad et al, 2011;Nawaz & Ashraf, 2007;Yamada et al, 2009). It was observed that compatible solutes such as Pro and GB had an important role in osmotic adjustment and protection of proteins, mitochondria, and chloroplast membranes under salt stress (Dawood, 2016;Takabe et al, 2006). Therefore, modification of negative effects of salinity by GB might be due to its protective role and antioxidant capacity against oxidative stress (Park et al, 2004).…”
Section: Resultssupporting
confidence: 88%
“…Similar to our findings, the reduction of MDA and H 2 O 2 contents were also observed in some plants using GB(El-Samad et al, 2011;Nawaz & Ashraf, 2007;Yamada et al, 2009). It was observed that compatible solutes such as Pro and GB had an important role in osmotic adjustment and protection of proteins, mitochondria, and chloroplast membranes under salt stress (Dawood, 2016;Takabe et al, 2006). Therefore, modification of negative effects of salinity by GB might be due to its protective role and antioxidant capacity against oxidative stress (Park et al, 2004).…”
Section: Resultssupporting
confidence: 88%
“…Synthesis of such osmolytes via complex biosynthetic pathways not only utilizes huge C-skeleton but also incurs high energy cost. From ATP utilization's point of view, biosynthesis of GB is the least-energy-intensive process, whereas biosynthesis of trehalose requires maximum energy (Dawood, 2016). Interestingly, under saline condition, elemental sodium itself can serve as an osmolyte and aid in maintaining the osmotic potential (Yeo and Flowers, 1986;Glenn et al, 1999;Chakraborty et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…The phenolic compounds that were upregulated in S. bicolor plants under drought stress post treatment with each of the five selected rhizobacterial isolates included the hydroxycinnamic acids and -conjugates: caffeoylshikimate, caffeoylquinate, coumaroylquinate, hesperetin, hydroxyflavone, luteolin, naringenin, 1-Osinapoyl-beta-D-glucose and shikimic acid; the flavonoids quercetin, hesperetin, hydroxyflavone, luteolin and naringenin; the terpenoids loganin and secologanin; and the terpenoid quinones menaquinol, benzoquinol and ubiquinone (Karuppanapandian et al, 2011;Martinez et al, 2016). The group of osmolytes that were upregulated in primed S. bicolor plants included the amino acids proline (Szabados and Savouré, 2010), glutamic acid (Tari et al, 2013); and the amine choline (Dawood, 2016). Choline plays a critical role in plant stress resistance, mainly for enhancing glycine betaine synthesis and accumulation and improved leaf RWC.…”
Section: Discussionmentioning
confidence: 99%